A simple and high-performance supercapacitor based on nitrogen-doped porous carbon in redox-mediated sodium molybdate electrolyte. (10th March 2015) - Sun, Kanjun; Feng, Enke; Peng, Hui; Ma, Guofu; Wu, Yajuan; Wang, Haiping; Lei, Ziqiang
Graphical abstract: Highlights: The eco-friendly polyaspartic acid is used as a precursor for nitrogen-doped porous carbon. Redox-mediated Na2 MoO4 is introduced in H2 SO4 aqueous solution to form mixture electrolyte. The supercapacitor exhibits high specific capacitance 841 F g −1 and energy density 378.5 Wh kg −1 . Abstract: Nitrogen-doped porous carbon derived from polyaspartic acid is utilized as activated carbon (AC) electrode for supercapacitor. The BET surface area and pore volume of the AC as high as 1071 m 2 g −1 and 0.61 cm 3 g −1 . The AC electrode in 1 M H2 SO4 electrolyte delivers high specific capacitance of 177 F g −1 at a high current density of 15 A g −1 . Surprisingly, by introducing redox-mediated 0.6 g Na2 MoO4 into 40 ml 1 M H2 SO4 as a mixture electrolyte, the specific capacitance of the supercapacitor improved 841 F g −1, about 375.1% of specific capacitance in 1 M H2 SO4 electrolyte. The high energy density 378.5 Wh kg −1 is also obtained. Furthermore, the AC electrode in the redox active Na2 MoO4 electrolyte shows the excellent capacitance retention of 88.2% for over 1000 cycles. These improved performance are owed to the redox reaction between Mo(VI)/Mo(V) and Mo(VI)/Mo(IV) redox couples in the mixed H2 SO4 and Na2 MoO4 electrolyte at the electrode|electrolyte interface, and the concentration of the Na2 MoO4 can also influence the electrochemical performance of the supercapacitor. Based on the overall performance, it is believed that the combination of polyaspartic acid derived nitrogen-doped porous carbon and redox active Na2 MoO4 electrolyte is more attractive in the near future for high performance energy-storage devices.